Information pollution and the war in Gaza: implications for Singapore - Wong, Yasmine (2024)
The Israel-Hamas war has seen the warring parties as well as other state and non-state actors disseminate biased and false information. This has clouded the information landscape surrounding the conflict. Besides demonstrating various disinformation types and tactics, there is also the increased resonance of certain disinformation narratives as they overlap and impact on societal sensitivities and identity-based fault lines. These are challenges for Singapore, as societal fault lines present vulnerabilities for disinformation penetration, ultimately affecting social cohesion.